Soft computing based approach to evaluate the performance of solar PV module considering wind effect in laboratory condition - Subhash Chandra; Sanjay Agrawal; D. S. Chauhan (Energy Reports, 2018)
Energy is the key factor for the growth of any country. Per capita energy consumption is the significance of the progress of any nation. With the increasing environmental impacts, word community is searching the way to shift towards sustainable energy sources. Recently the penetration of photovoltaic systems has increased to generate the electricity at grid or local level. Although this technology has improved a lot however the performance of these systems is site dependent. The experiment is conducted in laboratory of GLA University, Mathura, UP, India (hot and dry climate zone of India). Two PV modules of same electrical and mechanical specifications are taken for experiment. To analyze actual performance; different months of a year from various seasons are chosen including artificial wind. It has been observed that increased module temperature reduces performance but the cooling mechanism provided, bring down the module temperature due to which a net energy gain is 5.07% in considered time. Performance measure indices i.e. PR is improved by 3.4%. Experimental and Simulated energy is 431.28wh and 434.98wh for cooled module while for not cooled module experimental and simulated energy is 410.44wh and 439.7wh. Simulated values of energy are closer to experimental values for cooled module hence ANN avoids the underestimation of performance and overestimation of size, average simulated PR is also same as that of experimental PR i.e. 98.6%.
Keywords: 330; Back propagation; Energy; Performance ratio; Photovoltaic; Wind